AB0008 Cross-talk between bone turnover and cardiovascular disease. association of micrornas expression, fracture and abdominal aortic calcifications. (12th June 2018) - Pickering, M.-E.; Croset, M.; Millet, M.; Sornay-Rendu, E.; Rousseau, J.-C.; Borel, O.; Szulc, P.; Chapurlat, R.
Abstract : Background: MicroRNAs (miRs) have emerged as pivotal epigenetic key actors of gene regulation and several miRs have been shown to be at the crossroads of angiogenesis and of bone turnover, taking part in the calcification process by acting on osteoblasts and osteoclasts. 1 Calcification of the aortic media is highly regulated and involves numerous factors, including calcium deposal and other bone remodelling factors. 2 Objectives: The objective of this study was to find a signature of miRs linked both to osteoporotic fracture risk and abdominal aortic calcification (AAC). The first outcome was the link between miRs levels at baseline and incident osteoporotic fractures (IOF) during 20 years; the second outcome was the link between miRs levels at baseline and the increase in AAC during 17 years. Methods: Post-menopausal women older than 50 years from the OFELY cohort (Os des FEmmes de LYon) were selected if they had available serums at inclusion, and available data for each outcome. 3 miRs selected after literature review because of their impact on vascular calcification and bone turnover (miRs 26a-5p, 34a-5p, and 223–5 p) were measured at baseline. Bioassays of miRs was conducted with miRCURY Biofluids (Exiqon) extraction kit, TaqMan Life Technologies protocol, and QuantStudio 7 flex (Applied Biosystems) for RNA quantification. Results are expressed by relative quantification of Cycle threshold (Ct). Results: A sample of 434 age-matched women (63 [57–72] years old), 50% with incident osteoporotic fracture during the 20 years of follow-up, was included. 183 women had available data to explore AAC; 93 had an increase in Kauppila score in 17 years (58 [55–61] years old), 90 did not (55 [53–58] years old). No significant link was underlined between miRs and IOF (miR-26: 1.06 [0.85–1.27] vs 0.99 [0.85–1.17], p=0.07; miR-34: 1.15 [0.53–1.87] vs 1.26 [0.60–2.07], p=0.35; miR-223: 1.01 [0.68–1.43] vs 1 0.05 [0.72–1.56], p=0.32). No miR was significantly linked to an increase in AAC (miR-26: 1.09 [0.94–1.28] vs 1.10 [0.89–1.30], p=0.95; miR-34: 0.78 [0.46–1.21] vs 0.73 [0.38–1.50], p=0.90; miR-223: 0.97 [0.69–1.22] vs 0.78 [0.56–1.22], p=0.11). Conclusions: No association was observed between the 3 tested miRs and IOF or increase in AAC. Larger studies are necessary to select interesting epigenetic pathways reproductible on wider population. References: [1] Krzeszinskia JY, Wei W, Huynh H, Jin Z, Wang X, Chang T-C, et al. miR-34a Blocks Osteoporosis and Bone Metastasis by Inhibiting Osteoclastogenesis and Tgif2. Nature2014Aug 28;512(7515):431. [2] Szulc P. Abdominal aortic calcification: A reappraisal of epidemiological and pathophysiological data. Bone2016Mar;84:25–37. Disclosure of Interest: None declared